Aristolochic acid nephropathy: A scientometric analysis of literature published from 1971 to 2019. Issue 27 (9th July 2021) - Ji, Hongjian; Hu, Jingyin; Zhang, Guozhe; Song, Jianxiang; Zhou, Xiaohua; Guo, Dean
Abstract: Background: Aristolochic acid nephropathy (AAN) is a type of drug-induced nephropathy that may result in acute kidney injury and is associated with a potentially progressive course of kidney fibrosis and upper tract urothelial carcinoma. Aristolochic acids (AAs) are a group of toxins commonly present in plants of the genera Aristolochia and Asarum, which are found worldwide. AAN still occurs in Asian and Balkan regions. The progressive lesions and mutational events initiated by AAs are irreversible, and no effective therapeutic regimen for AAN has been established. Furthermore, more people are at risk of this disease due to casual exposure to AAs. This study performed a scientometric analysis of global research literature focusing on AAN. Methods: The Web of Science database was searched to identify all publications pertaining to "aristolochic acid nephropathy" or "Balkan endemic nephropathy" using these terms as key words to search the literature from 1971 to 2019. The collected data included the document type, author, journal, publication year, citation reports, and country of publication, and were analyzed using the VOSviewer software. Results: A total of 1251 records were initially obtained. Publication types, including "meeting abstract, " "letter, " "editorial material, " and "proceedings paper" were excluded, which left 1083 publications comprising 923 articles and 160 reviews. English was the predominant language of the publications. China had the most number of articles published with 217 (20.0%), followed by the USA with 186 articles (17.2%), and Germany with 138 articles (12.7%). Kidney International, Food and Chemical Toxicology, and Toxins were the 3 most active journals in publishing articles related to AAN. The total number of citations received by all publications was 39, 970, with an average of 36.91 citations per article (range: 0–1769). The literature mainly focused on apoptosis, oxidative stress, and inflammation in AAN. Conclusion: This study indicated that AAN is a significant topic in nephrology research, as shown by the large number of publications. The literature has mainly focused on the mechanisms of AA-induced nephropathy.